2018
DOI: 10.1016/j.bja.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts of fluid management in enhanced recovery pathways

Abstract: Perioperative fluid management impacts outcomes and plays a pivotal role in enhanced recovery pathways (ERPs). There have been major advances in understanding the effects of fluid therapy and administration during the perioperative period. Improving fluid management during this period leads to a decrease in complications, decrease in length of stay (LOS), and enhanced patient outcomes. It is important to consider preoperative and postoperative fluid management to be just as critical as intraoperative managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 59 publications
2
104
0
7
Order By: Relevance
“…The present study focused on IV fluid administration rather than urine output as a guidance parameter, since low urine output by itself is no longer considered harmful . Srinivasa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study focused on IV fluid administration rather than urine output as a guidance parameter, since low urine output by itself is no longer considered harmful . Srinivasa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on IV fluid administration rather than urine output as a guidance parameter, since low urine output by itself is no longer considered harmful [25,26]. Srinivasa et al described no difference in urine output between patients monitored by goal-directed fluid therapy (GDFT) and patients with restrictive fluid management [27].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic preload variables such as pulse pressure variation (PPV), stroke volume variation (SVV), and the plethysmographic variability index (PVI) are commonly used for predicting fluid responsiveness and are applied for intraoperative goal‐directed fluid therapy in high‐risk patients . We previously reported that the ability of dynamic preload variables to predict fluid responsiveness in adult patients with liver cirrhosis was reduced, which may be because liver cirrhosis induces low systemic vascular resistance; nevertheless, PPV, SVV, and PVI remain clinically applicable for adult patients with liver cirrhosis .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be argued that GDT allows the judicious use of fluid when it is needed. Moreover, it prevents unnecessary fluid loading when hemodynamic targets are already met (70). This personalized and prompt strategy can explain the reduction of postoperative complications in low-risk patients.…”
Section: Discussionmentioning
confidence: 98%